The comorbidity of disruptive mood dysregulation disorder in autism spectrum disorder. (30th July 2016) - Pan, Pei-Yin; Yeh, Chin-Bin
Highlights: The chronic irritability in youth with autism is often prominent and bothersome. The highlight of comorbid DMDD in ASD helps provide interventions for them. The existence of DMDD in ASD leads to further approach for pathobiology of the brain.